Communication Conflict in the Inculturation of Saparan Bekakak Custom in Ambarketawang Village - Anshori, Muhammad; Ridho, Ali; Amri, Yasirul; Masri, Muhammed Sharin Haji (Dialogia, 2023)
In various regions of Indonesia, cultural communication disputes are frequent, and the very existence of culture serves as a symbol for preserving that culture. Differences in beliefs are the source of conflict during cultural inculturation at the Saparan Bekakak traditional event; as a result, communication issues need to be resolved for the sake of culture, existence, and sustainability. The Ambarketawang Village, Sleman Regency, residents, and the village government were interviewed, observed, and documented in this descriptive qualitative research method. First, this study found community conflicts over how the Saparan Bekakak traditional event made communicating difficult for people with different cultural beliefs. Second, differences in interpretation of the Saparan Bekakak event make cultural inculturation a problem; third, the non-verbal arguments that arise from the symbols used in the traditional Saparan Bekakak event; fourth, the village government's role as an arbitrator or communicator in resolving Saparan Bekakak-related communication disputes. The disagreement over communication will be resolved, preventing any misinterpretation of meaning and preserving the traditional culture of Saparan Bekakak.